PERAN PERDAGANGAN INTERNASIONAL DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI NEGARA - Elsa Nurhabibi; Rihma Hani, Suci Wulandari, Ulfa Rahmayani Assyfa Hasibuan; Dwita Sakuntala (CV. ADIBA AISHA AMIRA, 2025)
This research aims to review the strategic role of international trade in encouraging Indonesia's economic growth and creating long-term economic stability. Using qualitative methods based on literature studies, this research explains the relationship between international trade, especially export and import activities, to gross domestic product (GDP) and national economic welfare. Based on 2023 data, Indonesia's trade balance shows a surplus of USD 31.22 billion, driven by the non-oil and gas sector with a contribution of USD 47.02 billion, although the oil and gas sector experienced a loss of USD 15.80 billion. This research also discusses international trade theories, such as absolute and comparative advantage, which are the basis for maximizing the benefits of global trade. The analysis results show that international trade provides great opportunities, such as global market access, technological improvements and innovation, as well as expanding employment opportunities. But challenges remain, including dependence on oil and gas imports and fluctuating commodity prices. The results of the discussion confirmed that international trade is an important pillar in encouraging Indonesia's economic growth, as long as it is managed with policies oriented towards sustainability and economic independence